2021
DOI: 10.3390/molecules26144145
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Molecular Docking Study of Volatile Constituents from Different Aromatic Lamiaceous Plants Cultivated in Madinah Monawara, Saudi Arabia

Abstract: A comparative study of volatile constituents, antioxidant activity, and molecular docking was conducted between essential oils from Mentha longifolia L., Mentha spicata L., and Origanum majorana L., widely cultivated in Madinah. The investigation of volatile oils extracted by hydrodistillation was performed using Gas Chromatography-Mass Spectrometry (GC-MS). A total number of 29, 42, and 29 components were identified in M. longifolia, M. spicata, and O. majorana representing, respectively, 95.91, 94.62, and 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
(75 reference statements)
0
12
0
Order By: Relevance
“…Table 4 shows that all of constituents are not able to interfere with CYP2D6 and CYP3A4 and would not be metabolized by either. The excretion parameters showed that the total clearance (0.103 and 1.363 log mL/min/kg) achieved positive values, meaning a quick excretion [ 15 ]. Volatile organic compounds can influence the expression and activity of cytochrome P450 enzymes and transferases involved in the metabolism of other drugs in the system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 shows that all of constituents are not able to interfere with CYP2D6 and CYP3A4 and would not be metabolized by either. The excretion parameters showed that the total clearance (0.103 and 1.363 log mL/min/kg) achieved positive values, meaning a quick excretion [ 15 ]. Volatile organic compounds can influence the expression and activity of cytochrome P450 enzymes and transferases involved in the metabolism of other drugs in the system.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, computational models such as molecular docking are carried out as a bioinformatic tool to study the inhibition of several enzymes that negatively affect the antioxidant activity, such as xanthine oxidase, nitric oxide synthases (NOS), cytochrome P450 reductase, and nicotinamide-adenine dinucleotide phosphate (NADPH) oxidase, as well as the mitochondrial electron transport chain. Furthermore, it is known that reactive oxygen species (ROS) generation occurs in the mitochondria via oxidative phosphorylation and through the enzyme NADPH oxidase [ 15 ]. Additionally, NADPH oxidase-mediated cell proliferation participates in intracellular signaling processes and has been observed in a variety of cancer cells and in tissue repair processes [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The result that was obtained is in line with the findings of other studies as well. 41,42 This demonstrates that compound Wal can prevent the action of NO enzyme in producing superoxide.…”
Section: Resultsmentioning
confidence: 92%
“…The profiles of interaction and visualization were performed for the best-docked complexes using Discovery Studio software (Ver. 21.1.0.20298) [ 63 ].…”
Section: Methodsmentioning
confidence: 99%